Jurisdictional Authority of Religious Courts in Consumer Protection Cases Within The Islamic Economic Framework: A Normative Legal Study - Arisandhi, Imamul Muttaqin; al-Islam, Majid; Ulum, Bahrul (LPPPM STAI Darul Hikmah Bangkalan, 2025)
The rapid development of the Islamic economic system in Indonesia has raised significant legal concerns, particularly regarding consumer protection disputes within Islamic financial institutions. The jurisdictional competence of Religious Courts in adjudicating such disputes has been a subject of legal debate, given the apparent contradiction between the Consumer Protection Act (Law No. 8 of 1999), which designates General Courts as the competent forum, and the Religious Courts Act (Law No. 3 of 2006), which establishes the exclusive jurisdiction of Religious Courts over Islamic economic matters. This study employs a normative juridical approach, analysing relevant legislation and judicial decisions to clarify the legal position of Religious Courts in resolving consumer protection disputes in Islamic finance. The findings indicate that the Constitutional Court’s ruling affirms the exclusive jurisdiction of Religious Courts over Islamic economic disputes, rendering the provisions of the Consumer Protection Act regarding General Court jurisdiction inapplicable in such cases. However, discrepancies in judicial interpretations and procedural inconsistencies highlight the need for legislative harmonisation and judicial capacity-building. This study concludes that comprehensive legal reform is required to reinforce the authority of Religious Courts in consumer protection matters within the Islamic economic framework